Quantitation of Human 14-3-3ζ Dimerization and the Effect of Phosphorylation on Dimer-monomer Equilibria - Trošanová, Zuzana; Louša, Petr; Kozeleková, Aneta; Brom, Tomáš; Gašparik, Norbert; Tungli, Ján; Weisová, Veronika; Župa, Erik; Žoldák, Gabriel; Hritz, Jozef (Journal of molecular biology, 2022)
14-3-3 proteins are universal regulatory proteins and their function depends on their oligomeric form which may alter between the monomeric, homodimeric and heterodimeric states. The populations of individual oligomeric forms are controlled by Kd values of the dimer-monomer equilibria between the involved isoforms. This complex picture is extended by post-translational modifications, e.g. phosphorylation. In this work, we describe the equilibria between monomers, homo- and heterodimers of the 14-3-3ζ isoform in the unmodified and phosphorylated form. To cover a wide range of dimerization affinities, we combined solution NMR, microscale thermophoresis, native PAGE, and a set of novel fluorescence assays. Using a FRET based assay, we also determined the kinetic parameters of dimerization. We found that phosphorylation of 14-3-3ζ at Ser58 increases its homodimeric Kd value by 6 orders of magnitude. The presented assays allow to efficiently monitor 14-3-3ζ dimerization as a function of external factors, such as temperature, salt concentration, and client protein binding. For instance, we obtained values of both transient and equilibrium thermodynamic constants for the dimerization, and observed a substantial decrease of 14-3-3ζ dimer dissociation rate upon binding to the doubly phosphorylated regulatory domain of tyrosine hydroxylase. In summary, our work provides a conceptual framework to characterise the isoform exchanges of homo- and heterodimers which can significantly deepen our knowledge about the regulatory function of 14-3-3 proteins.
Keywords: termodynamika; Protein Multimerization; dimerization; Thermodynamics; multimerizace proteinu; 14-3-3; fosforylace; NMR; Humans; phosphorylation; proteiny 14-3-3; Protein Binding; 14-3-3 Proteins; Phosphorylation; vazba proteinů; lidé; dissociation constant; FRET